A literatura silenciada na escola : a violência de assédio e abuso sexual no Ensino de Literatura Juvenil - Aguiar, Hellen Jacqueline Ferreira de Souza Dantas de (2024)
The present research aims to verify how the reading practices of fractured themes present in literature aimed at young people in municipal schools in the city of Campina Grande, in the state of Paraíba, take place. Employing an exploratory qualitative and interpretive approach, the study investigates the presence (or lack thereof) of fractured themes, particularly those related to sexual harassment and abuse against young people, in Brazilian literature and classrooms. Specifically, the research examines the reading practices of Portuguese language teachers from four schools, encompassing grades 6 to 9 of elementary school, located in different geographic regions of Campina Grande. Documents such as the National Common Curricular Base (BNCC) 2010, National Curricular Guidelines, and National Curricular Parameters were analyzed, along with questionnaires administered to teachers. Data analysis was conducted theoretically, discussing fractured themes within the classroom perspective, drawing upon the works of Cosson (2013), Machado (2009), Brazil (2020, 2021), Resende (2008), Riche (2010), Ramos (2010), Doll (2017), among others. The findings indicate that fractured themes are not yet integrated into Portuguese language teacher training, and consequently, are absent from classroom discussions. This outcome reflects societal pressures that impose a silent and questionable "protection" of taboo subjects in classrooms, hindering reflection, discussion, and potentially, the protection of these young people through the open exploration of these themes. The results of this research can significantly contribute to the development and strengthening of theories and discussions on the importance of preparing teachers to address these issues in the classroom, as well as informing public policies aimed at teacher training, initiatives, and pedagogical practices.